EVALUATION OF TOTAL PHENOLIC AND FLAVONOID CONTENT IN GONAD OF SEA URCHIN Stomopneustes variolaris AND SEAWEEDS - MAHESHKUMAR, K.; SHANMUGAM, A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The Phenolic and Flavonoids are bioactive compounds which exhibit several biological effects such as anti-inflammatory, anti-hepatotoxic and anti-ulcer actions. In the present study total phenolic and flavonoid content was estimated in the gonads of sea urchin Stomopneustes variolaris collected from Arokiyapuram, Kanyakumari dt. (Tamilnadu, India). Seaweeds collected from the feeding grounds of S. variolaris were also analyzed for total phenolic and flavonoid content. The total phenolic and flavonoid content of the gonad was 59.3±3.4 and 18±1.3 mg/100 g tissue respectively. In seaweeds, phenolic content was ranged from 12.5±2.1 (Chaetomorpha media) to 16.4±2.1 mg GAE/100 g (Stoechospermum marginatum). Total flavonoid content in Sargassum wightii, Stoechospermum marginatum (Brown algae), Gracilaria corticata, G. verrucosa (Red algae), Chaetomorpha media, Enteromorpha compressa, Ulva lactuca (Green algae) were 4.1±1.2, 4.3±1.0, 3.7±1.4, 4.1±0.5, 3.2± 1.1, 4.0± 0.4 and 4.0± 0.5 mg RE/100 g respectively.